A comparative magnetic resonance spectroscopy study of GABA+ and glutamate referenced to creatine and phosphocreatine in the left dorsolateral prefrontal cortex of perimenopausal women and women of reproductive age - Tran, Kim H.; Luki, Jessica; Hanstock, Sarah; Hanstock, Christopher C.; Seres, Peter; Aitchison, Katherine; Shandro, Tami; Le Melledo, Jean-Michel (Frontiers in Psychiatry, 2022)
Objective: The perimenopause is associated with an increased risk of developing a major depressive (MD) episode. The biological changes occurring during perimenopause responsible for this increased risk of depression remain to be elucidated. Postmortem and magnetic resonance spectroscopy (MRS) studies have revealed decreased gamma-aminobutyric acid (GABA) and glutamate (Glu) levels in the dorsolateral prefrontal cortex (DLPFC) of MD patients. The objective of this study was to compare LDLPFC GABA+ and Glu ratios (referenced to creatine and phosphocreatine) in healthy reproductive-aged (RD) and perimenopausal (PM) women. Methods: 18 healthy PM and 20 RD women were included in the study. Our dependent variables, LDLPFC GABA+ and Glu ratios, which include homocarnosine and macromolecules, were measured via MRS, using a 3 Tesla magnet. Absence of current or past psychiatric diagnosis was confirmed via a structured interview. RD participants were scanned during the early follicular phase of the menstrual cycle (MC). PM women were scanned outside of ovulatory cycles. Results: Mean LDLPFC GABA+ and Glu ratios were not statistically different between the PM group and RD group (PM mean = 0.100.06, RD mean = 0.110.04, t = –0.383, df = 36, d = -0.13, p = 0.70), (PM mean = 0.56 0.06, RD mean = 0.57 0.05, t = –0.794, df = 36, d = -0.26, p = 0.43), respectively. The perimenopause demarcates the end of the reproductive life. Unsurprisingly PM women were older than RD women (PM women: 48.83.55 years, range 41–53 years old; RD women: 31.5 9.66 years, range 18–47 years old) (p < 0.001). This inherent entanglement of group and age is a limitation of our study. Conclusion: Contrary to our previous findings of decreased GABA+ and Glu in the medial prefrontal cortex in perimenopausal women, the perimenopause is not associated with decreased GABA+ or Glu ratios in the LDLPFC. This suggests that brain areas playing a role in MD display different sensitivity to the female hormones fluctuations associated with perimenopause.